2021
DOI: 10.1002/cnr2.1538
|View full text |Cite
|
Sign up to set email alerts
|

Early oral intake and early removal of nasogastric tube post‐esophagectomy: A systematic review and meta‐analysis

Abstract: Background: Early oral intake (EOI: initiated within 1 day) and early nasogastric tube removal (ENR: removed ≤2 days) post-esophagectomy is controversial and subject to significant variation.Aim: Our aim is to provide the most up-to-date evidence from published randomized controlled trials (RCTs) addressing both topics.Methods: We searched MEDLINE and Embase (1946-06/2019) for RCTs that investigated the effect of EOI and/or ENR post-esophagectomy with gastric conduit for reconstruction. Our main outcomes of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A meta-analysis by Weijs et al [ 13 ] reported similar results that hospital stay was significantly shorter with preoperative or early removal of NGT. However, a recent meta-analysis of six RCTs by Kaaki et al [ 18 ] found that early removal of NGT has no impact on length of stay (LOS), whereas early oral intake found shorter LOS. Hence, it is apparent that early oral feeding (EOF) can be initiated easily in the no NGT group to receive its benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Weijs et al [ 13 ] reported similar results that hospital stay was significantly shorter with preoperative or early removal of NGT. However, a recent meta-analysis of six RCTs by Kaaki et al [ 18 ] found that early removal of NGT has no impact on length of stay (LOS), whereas early oral intake found shorter LOS. Hence, it is apparent that early oral feeding (EOF) can be initiated easily in the no NGT group to receive its benefit.…”
Section: Discussionmentioning
confidence: 99%
“… 24 – 27 Also, early NGT removal does not seem to increase the risk of anastomotic leakage, as multiple meta-analyses evaluating early removal or even omission of the NGT have found no differences in anastomotic leakage rates. 6 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…With the development of fast track surgery and enhanced recovery after surgery (ERAS) programmes,6 there has been an increasing trend towards improved quality of life (QOL) following operation. Early oral intake (EOI), as one of the fundamental programmes in ERAS, has been confirmed as a safe and feasible procedure that improved clinical outcomes including faster recovery of bowel function in the perioperative care of gastrointestinal surgery, oesophagectomy and gynaecological surgery 7–9. Meanwhile, studies on these topics have also shown that EOI could shorten the length of hospital stay by 1.7 days and did not increase the occurrence of adverse complications 10.…”
Section: Introductionmentioning
confidence: 99%
“…Early oral intake (EOI), as one of the fundamental programmes in ERAS, has been confirmed as a safe and feasible procedure that improved clinical outcomes including faster recovery of bowel function in the perioperative care of gastrointestinal surgery, oesophagectomy and gynaecological surgery. [7][8][9] Meanwhile, studies on…”
Section: Introduction Background and Rationalementioning
confidence: 99%